Space weathering and the color–color diagram of Plutinos and Jupiter Trojans - Melita, Mario Daniel (2015)
The Jupiter Trojan asteroids and the Plutinos are two peculiar populations. They are dynamically resonant, therefore with heliocentric distances relatively bounded for long timescales, as a farely general rule. As a consequence, some correlation with the surface color properties of their respective members is expected. Indeed, there are apparent differences in the B-V vs. V-R color–color diagram of the two populations. Using a simple model based on the surface color due to the contribution of two components, one pristine and one altered, we find as plausible that the difference is due to the interplay of space weathering by energetic cosmic-radiation and collisional effects.